Strategic Issues in Time Dimension of Marketing Tools in Business to Business Markets - Gopal, R.K.; Raju, T.V (Ushus Journal of Business Management, 2021)
Key to success in serving industrial customers is to consider together the individual account, the full marketing mix, and the time. The individual account is fundamental to marketing. Marketing tools have time dimension. In general in effective marketing, the critical tools are those with time dimensions matching the time horizons of customers commitments. Long-term tools serve customers with long time horizons, whereas short term tools can support long-term tools in long-term relations. This paper attempts to understand the various marketing tools used by an industrial marketer and their time dimension. This will help the industrial marketer to deploy the marketing tools in an effective way.